2005
DOI: 10.1021/bp050098r
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing for a Nontagged F1‐V Fusion Protein as Vaccine Antigen against Bubonic and Pneumonic Plague

Abstract: A two-component recombinant fusion protein antigen was re-engineered and tested as a medical counter measure against the possible biological threat of aerosolized Yersinia pestis. The active component of the proposed subunit vaccine combines the F1 capsular protein and V virulence antigen of Y. pestis and improves upon the design of an earlier histidine-tagged fusion protein. In the current study, different production strains were screened for suitable expression and a purification process was optimized to iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
102
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 51 publications
9
102
1
1
Order By: Relevance
“…F1-V was originally purified using a polyhistidine tag and the his(10)-F1-V vaccine protected experimental mice against pneumonic as well as bubonic plague produced by either F1 + or F1 − strains of Y. pestis [5]. By a statistical comparison of potency [6], the recombinant fusion-protein vaccine provided far better protection against the wild-type (F1 + ) strain than did the former Plague Vaccine USP, and it also showed a significant improvement in protection over a cocktail vaccine composed of the separate F1 and V antigens, as was first indicated after its creation [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…F1-V was originally purified using a polyhistidine tag and the his(10)-F1-V vaccine protected experimental mice against pneumonic as well as bubonic plague produced by either F1 + or F1 − strains of Y. pestis [5]. By a statistical comparison of potency [6], the recombinant fusion-protein vaccine provided far better protection against the wild-type (F1 + ) strain than did the former Plague Vaccine USP, and it also showed a significant improvement in protection over a cocktail vaccine composed of the separate F1 and V antigens, as was first indicated after its creation [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the success of animal protection studies and with the intent to improve the fusion protein for product development, F1-V was subsequently re-engineered to remove the polyhistidine tag and placed under transcriptional control of the IPTG-inducible pET-24a expression system (plasmid pPW731) in Escherichia coli strain BL21 (DE3), and then purified from soft inclusion bodies using 6M urea and a two-column procedure including anionexchange and hydrophobic interaction chromatography [6]. The untagged fusion protein showed equivalent immunogenicity and protective efficacy, and was less polydisperse in molecular structure than the individual F1 subcomponent, but still showed a tendency to aggregate under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interest in potentially incorporating plague vaccination into the Colorado Division of Wildlife's lynx reintroduction protocol was motivated by these findings. Effective vaccines for preventing plague in mammalian species, including felids, have been developed only recently (Heath et al, 1998, Gasper andWatson, 2001;Rocke et al, 2004;Powell et al, 2005). Of these, a recombinant capsular F1-V fusion protein vaccine (Powell et al, 2005) has shown a promising combination of safety and efficacy in black-footed ferret recovery (Rocke et al, 2004(Rocke et al, , 2008 and appeared potentially useful in lynx restoration as well.…”
Section: Introductionmentioning
confidence: 99%
“…Effective vaccines for preventing plague in mammalian species, including felids, have been developed only recently (Heath et al, 1998, Gasper andWatson, 2001;Rocke et al, 2004;Powell et al, 2005). Of these, a recombinant capsular F1-V fusion protein vaccine (Powell et al, 2005) has shown a promising combination of safety and efficacy in black-footed ferret recovery (Rocke et al, 2004(Rocke et al, , 2008 and appeared potentially useful in lynx restoration as well. We report on assessment of responses to a recombinant F1-V fusion protein vaccine (US Army Medical Research Institute of Infectious Diseases, Fort Detrick, Frederick, Maryland, USA) in captive lynx being held in southwestern Colorado prior to release as part of a reintroduction program.…”
Section: Introductionmentioning
confidence: 99%